1981
DOI: 10.1007/bf00006210
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, distribution and seasonal periodicity of some aquatic fungi of Sat-Tal (Nainital), India

Abstract: The occurrence of 23 species of aquatic fungi belonging to Blastocladiales, Saprolegniales, Lagenidiales and Peronosporales in three lakes and their surrounding cultivated and non-cultivated soils of Sat-Tal area have been studied. The species were found to be different in their habitat and temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In India, Butler (1907) first report occurrence on the phycomycetes. Later on a large number of investigators have reported different species of this group, Bhargava (1946), Dayal and Thakurji (1968), Khulbe (1977), Mer (1980), Chowdhry and Agarwal (1980), Manoharachary (1981Manoharachary ( ,1991, Mer and Khulbe (1984), Mishra and Dwivedi (1987), Prabhuji and Shrivastava (1978), Sati (1997), Prasad Dei et al, (2009) and Shinde and Pawar (2015) etc. A wide variety of aquatic fungi such as zoophagales, Saprolegniales and Peronosporales are found in fresh water.…”
Section: Introductionmentioning
confidence: 99%
“…In India, Butler (1907) first report occurrence on the phycomycetes. Later on a large number of investigators have reported different species of this group, Bhargava (1946), Dayal and Thakurji (1968), Khulbe (1977), Mer (1980), Chowdhry and Agarwal (1980), Manoharachary (1981Manoharachary ( ,1991, Mer and Khulbe (1984), Mishra and Dwivedi (1987), Prabhuji and Shrivastava (1978), Sati (1997), Prasad Dei et al, (2009) and Shinde and Pawar (2015) etc. A wide variety of aquatic fungi such as zoophagales, Saprolegniales and Peronosporales are found in fresh water.…”
Section: Introductionmentioning
confidence: 99%